Blood Protein Polymorphism on Javanese Fat Tailed Sheep and Javanese Thin Tailed Sheep - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT The aim of this study is to know the genotype characteristic of Javanese Fat Tailed Sheep and Javanese Thin Tailed Sheep through electrophoresis methods, Sixty sliecps were used, which comprised arc 5 male and 25 female Javanese Fat Tailed Sheeps